2015
DOI: 10.5539/sar.v4n3p32
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Innovation in Organic Agriculture: A European Perspective Using Experience from the SOLID Project

Abstract: Organic farming is recognized as one source for innovation helping agriculture to develop sustainably. However, the understanding of innovation in agriculture is characterized by technical optimism, relying mainly on new inputs and technologies originating from research. The paper uses the alternative framework of innovation systems describing innovation as the outcome of stakeholder interaction and examples from the SOLID (Sustainable Organic Low-Input Dairying) project to discuss the role of farmers, researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Since providing information and knowledge is costly, increased public efforts in the direction of increased free access to information resources as well as increased provision of information, advisory, and extension services are paramount to the adoption of sustainable production strategies in the dairy supply chain. Farmer-led research could be an effective way for researchers and the farmer together to develop sustainability of agriculture [38]. In the future, the role of information sharing practices is likely to become increasingly crucial to achieve higher levels of sustainability-in all domains: environmental, economic, and social-of supply chains, even outside of the agro-food sector.…”
Section: Discussionmentioning
confidence: 99%
“…Since providing information and knowledge is costly, increased public efforts in the direction of increased free access to information resources as well as increased provision of information, advisory, and extension services are paramount to the adoption of sustainable production strategies in the dairy supply chain. Farmer-led research could be an effective way for researchers and the farmer together to develop sustainability of agriculture [38]. In the future, the role of information sharing practices is likely to become increasingly crucial to achieve higher levels of sustainability-in all domains: environmental, economic, and social-of supply chains, even outside of the agro-food sector.…”
Section: Discussionmentioning
confidence: 99%
“…Since providing information and knowledge is costly, increased public efforts in the direction of increased free access to information resources as well as increased provision of information, advisory and extension services are paramount to the adoption of sustainable production strategies in the dairy supply chain. Farmer-led research could be an effective way for researchers and the farmer together to develop sustainability of agriculture [35].…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen participatory projects were conducted with close collaboration between farmers and researchers, covering various strategies related to feeding and forage, natural resource use, environmental and animal management. The experience showed that such a collaborative approach contributes to developing practical knowledge about sustainable organic and low‐input dairying (Padel et al ., ) (see Box 2).…”
Section: Innovations To Increase Efficiency In Organic and Low‐input mentioning
confidence: 99%